Utilization of Social Issues in PBL to Improve Problem-Solving Abilities of High School Students in Ecosystem Material - Rahmawati, Kamalia Nurazizah; Saptono, Sigit; Peniati, Endah (FMIPA UNNES, 2018)
Problem-solving skills related social-scientific issue in society’enviroment need to be owned by students. This capability can be trained by PBL (Problem Based Learning) model. The purpose of this research is to analyze problem solving abilities of students. The type of this research is quasi experiment with one group pretest-posttest design. Sample of the research is X grade students from SMA N 1 Semarang and SMA Ksatrian 1 Semarang. The result consisted of primary outcome in the form of capability, N-gain value and classical content mastering as well as secondary outcome covering the implementation of learning, teacher's response and student's response. Based on the result, the average of problem solving ability SMA N 1 Semarang increased from 70% to 79,5%, while SMA Ksatrian 1 Semarang increased from 59,5% to 73%. Completeness of classical learning SMA N 1 Semarang, class X MIPA 7, 97% and class X MIPA 9, 79%. The completeness of classical learning SMA Ksatrian 1 Semarang, class X MIPA 3, 80% and class X MIPA 5, 65%. N-gain value of SMA N 1 Semarang 0,553 and SMA Ksatrian 1 Semarang 0,433 in medium category. The conclusion of this research is the utilization of social issue with PBL model can improve problem solving ability on ecosystem’learning in SMA.